Renal Resistive Index and mortality in critical patients with acute kidney injury. (March 2016) - Boddi, Maria; Bonizzoli, Manuela; Chiostri, Marco; Begliomini, Dario; Molinaro, Adele; Tadini Buoninsegni, Laura; Gensini, Gian Franco; Peris, Adriano
Abstract: Background: The predictive role of Doppler Renal Resistive Index (RRI) for mortality was shown in chronic kidney disease. In selected populations of intensive care unit (ICU), RRI predicts acute kidney injury (AKI) occurrence and anticipates persistent AKI. No data are available about mortality. We investigated whether RRI assay at AKI diagnosis could predict AKI mortality in a 10‐bed‐mixed medical–surgical and trauma ICU of a tertiary referral teaching hospital. The association between RRI and persistent AKI at discharge was investigated. Methods: One hundred and twenty‐five of 1512 patients admitted from January 2010 to March 2013 who developed AKI during ICU stay were enrolled. Kidney function was evaluated daily according to risk, injury, failure, loss and end‐stage criteria. At AKI diagnosis, we measured RRI. The association between RRI at AKI diagnosis and ICU death or persistent AKI at ICU discharge was analysed by multivariable logistic regression analysis. Results: At AKI diagnosis, RRI was 0·77 (0·70–0·88) in survivors and 0·85 in nonsurvivors (0·79–0·94) ( P = 0·002). RRI values were significantly associated with ICU death (OR = 1·63–95% CI 1·06–2·49, P = 0·025). A RRI cut‐off value of 0·77 was identified by receiver operating characteristic curve. Multivariate analysis selected RRI and abdominal hypertension as strongest predictors of AKI mortality. At AKI diagnosis, RRI was 0·78 (0·70–0·85) or 0·85 (0·73–0·92) ( P = 0·026) in patients with or without persistent AKI at discharge. Multivariate analysis selected RRI at AKI diagnosis as the strongest predictor of persistent AKI. Conclusions: High RRI values at AKI diagnosis are strictly and independently associated with in‐ICU mortality and persistent AKI at ICU discharge.